Associations between dairy protein intake and body weight and risk markers of diabetes and CVD during weight maintenance. Issue 5 (14th March 2014) - Bendtsen, Line Q.; Lorenzen, Janne K.; Larsen, Thomas M.; van Baak, Marleen; Papadaki, Angeliki; Martinez, J. Alfredo; Handjieva-Darlenska, Teodora; Jebb, Susan A.; Kunešová, Marie; Pfeiffer, Andreas F. H.; Saris, Wim H. M.; Astrup, Arne; et al.
<x content-type="archive" xml:space="preserve">Abstract</x> Dairy products have previously been reported to be associated with beneficial effects on body weight and metabolic risk markers. Moreover, primary data from the Diet, Obesity and Genes (DiOGenes) study indicate a weight-maintaining effect of a high-protein–low-glycaemic index diet. The objective of the present study was to examine putative associations between consumption of dairy proteins and changes in body weight and metabolic risk markers after weight loss in obese and overweight adults. Results were based on secondary analyses of data obtained from overweight and obese adults who completed the DiOGenes study. The study consisted of an 8-week weight-loss phase and a 6-month weight-maintenance (WM) phase, where the subjects were given five different diets varying in protein content and glycaemic index. In the present study, data obtained from all the subjects were pooled. Dairy protein intake was estimated from 3 d dietary records at two time points (week 4 and week 26) during the WM phase. Body weight and metabolic risk markers were determined at baseline (week − 9 to − 11) and before and at the end of the WM phase (week 0 and week 26). Overall, no significant associations were found between consumption of dairy proteins and changes in body weight and metabolic risk markers. However, dairy protein intake tended to be negatively associated with body weight gain (P= 0·08; β = − 0·17), but this was not persistent when controlled for total protein intake, which indicates that dairy protein adds no additional effect to the effect of total protein. Therefore, the present study does not report that dairy proteins are more favourable than other proteins for body weight regulation.